Suillus punctipes Singer, Farlowia 1945 - Palamarchuk, Marina A.; Kirillov, Dmitry V.; Shadrin, Dmitry M. (Zenodo, 2021)
Suillus punctipes (Peck) Singer, Farlowia 2 (2): 277 (1945) (Fig. 4 a, b) Pileus 30–80 mm in diam., convex, then expended, when young covered by tufts of brown tomentum, soon becoming glabrous, sticky, bright yellow-brown, brownish-yellow, ochraceous-orange, fulvous. Hymenophore as tubes, adnate or slightly decurrent, very thin, 4–6 mm in width, brown, gray-brown, then dirty-brown-yellow or brownish-yellow. The hymenophore of young specimens exuding white droplets when fresh. Stipe 50–100 × 15 mm, cylindrical to clavate, yellow-brown, light ochraceous-orange, all covered with round, sticky glandular dots. The glandular dots on the stem remain white for a long time, only browning when bruised and in old specimens. Flesh white in pileus, pale orange in stipe; taste not distinctive. Smell fragrant, tarry and strong. Basidia 16–25 × 5–7.5 μm, clavate, 2- and 4-spores. Basidiospores (7)7.5–10 × 3–3.5 μm, Q = 2–3, fusiformellipsoidal, yellowish-brown. Cystidia (cheilo-, pleuro- and caulocystidia) 30–70 × 6.5–10 μm, clavate or fusiform, hyaline or with dark-brown content. Pileipellis consisting of parallel or slightly diverging pale yellowish-brown hyphae 5–8 μm diam., immersed in gelatinous substance. Clamp connections absent in all tissues. Ecology and distribution . The species is widely distributed in North America, where it forms ectomycorrhizae with Pinus strobus (Smith & Thiers 1964; Roody 2003). In Russia, it was found in Baikal region (Nezdojminogo 1969; Petrov 1991; Gorbunova & Stepanova 2015), Magadan (Vassilkov 1971; Sazanova 2009), Primorsky Kray (Vasilyeva 1973), Altai (Kovalenko1992), Northern Urals (Perevedentseva 2008), and West Siberia (Zvyagina 2008). It is believed that the species forms ectomycorrhizae with Pinus sibirica and P. pumila . Collection examined . RUSSIA, Troitsko-Pechorsky district, Pechoro-Ilychsky Nature Reserve, 12 km upstream the Pechora River from settlement Yaksha, 61°47’30.0”N, 57°04’18.0”E, green moss pine forest with Pinus sibirica , 18 Aug. 2000, col. M. Palamarchuk , SYKOf 2275; the same location, 61°47’31.3”N, 57°03’21.2”E, spruce green moss forest with Pinus sibirica , 16 Aug. 2015, col. M. Palamarchuk , SYKOf 2669; 6 km upstream the Pechora River from cordon Shezhym-Pechorsky, 62°03’39.2”N, 58°28’4.1”E, spruce green moss forest with Pinus sibirica , 12 Aug. 2019, col. M. Palamarchuk , SYKOf 3143. Vuktyl district, “Yugyd va” National Park, basin of the Schugor River, Nizhnie Vorota, left bank, 1.5 km upstream, 64°12’48.3”N, 58°00’22.3”E, spruce green moss forest with Pinus sibirica , 10 Aug. 2016, col. M. Palamarchuk , D. Kirillov , SYKOf 2598, ibid., 15 Aug. 2016, col. M. Palamarchuk , D. Kirillov , SYKOf 2560; ibid., afforested top of the rock, 64°12’52.4”N, 57°57’43.1”E, spruce green moss forest with Pinus sibirica , 12 Aug. 2016, col. M. Palamarchuk , D. Kirillov , SYKOf 2593. Note . Suillus punctipes is very similar to S . plorans due to the yellow-brown pileus and stipe with glandular dots. According to some authors, the color of mycelium at the base of stipe is one of the differences: S. plorans has pink mycelium, S. punctipes — white (Vasylkov 1971; Klofac 2013). But Vasylkov (1971), when comparing specimens from Baikal region with those from North America ( S. punctipes ), reported pink color of the base of stipe for both species. All our specimens of S. plorans and S. punctipes have white mycelium in the base of the stipe. Another difference is the smell. However, this feature cannot be considered conclusive since it varies greatly. A slight difference is observed in the size of the basidiospores—in S. plorans spores are wider (up to 4.5 μm), while their size is up to 3.5 μm in S. punctipes . Suillus punctipes can be recognized by the predominantly orange or ochraceous-orange tinge of basidiomata, numerous round glandular dots on stem, for a long time remained white. Basidiomata of S. plorans are predominantly yellow tinge and glandular dots on stem are brown. The species differ best on the structure of the pileipellis, the pileipellis of S. punctipes lack hyphae with dark brown content. : Published as part of Palamarchuk, Marina A., Kirillov, Dmitry V. & Shadrin, Dmitry M., 2021, Morphology and molecular data of the species of Suillus (Suillaceae, Boletales) associated with Pinus sibirica at the European northeast of Russia, pp. 18-34 in Phytotaxa 490 (1) on page 30, DOI: 10.11646/phytotaxa.490.1.2, http://zenodo.org/record/5756712 : {"references": ["Smith, A. H. & Thiers, H. D. (1964) A contribution toward a monograph of North American species of Suillus (Boletaceae). Ann Arbor, Michigan. 163 pp.", "Roody, W. C. (2003) Mushrooms of West Virginia and the Central Appalachians. Kentucky. 520 pp.", "Nezdojminogo, E. L. (1969) Ad floram Agaricalium litoris lacus Baical septentrionali-orientalis. Novosti sistematiki nizshikh rastenii 6: 146 - 158. [In Russian]", "Petrov, A. N. (1991) Synopsis of the flora of macromycetes of the Baikal region. Nauka, Novosibirsk. 81 pp. [In Russian]", "Gorbunova, I. A. & Stepanova, N. V. (2015) New about biota macromycetes of nature reserve Baikalo-Lenskiy. Plant Life of Asian Russia 4 (20): 3 - 11.", "Vassilkov, B. P. (1971) Batter mushrooms growing in cedar pine thicket of the USSR. Mikologiya i Fitopatologiya 5 (2): 184 - 186. [In Russian]", "Sazanova, N. A. (2009) Macromycetes of the Magadan Region. SVNC DVO RAN, Magadan. 196 pp. [In Russian]", "Vasilyeva, L. N. (1973) Mushrooms (Agaricales) of the Primorsky Kray. Nauka, Leningrad. 331 pp. [In Russian]", "Kovalenko, A. E. (1992) Ad floram agaricalium reservati Altaici. Novosti sistematiki nizshikh rastenii 28: 61 - 67. [In Russian]", "Perevedentseva, L. G. (2008) Synopsis of agaricoid basidiomycetes of the Perm Krai. Perm State Pedagogical University, Perm. 86 pp. [In Russian]", "Zvyagina, E. A. (2008) Preliminary data on the species composition of macromycetes in the basin of the river Salym. The Northern Region: Science, Education, Culture 2 (18): 23 - 30. [In Russian]", "Klofac, W. (2013) A world-wide key to the genus Suillus. Osterreichische Zeitschrift fur Pilzkunde 22: 211 - 278."]}